Merchandising rules for shelf space allocation with product categorization and vertical positioning - Czerniachowska, Kateryna; Subbotin, Sergey (Zasady przydzielania produktom miejsca na półkach sklepowych z uwzględnieniem kategoryzacji produktów i pozycjonowania pionowego, 2021)
Visual merchandising is assumed to be the main component of retailing; the significance of it is highlighted by academics and practitioners. This research focused on the in-store merchandising strategy of product allocations and describes the relations between such tactics and customers’ perception of store layout, traffic direction, brand awareness, and the appropriate assigning of products to shelf levels, based on their brand as well as price. For retailers, this study provides an overview of incorporating different merchandising tactics into a shelf space allocation model which is applicable at stores selling branded and popular 35fast-moving products. The authors carefully adapted the product allocation approach on the planogram, as well as the way in which products could be placed on different shelf levels. This model satisfies the retailers’ goals and may have a significant effect on sales. Thus, the study provides essential insights into the influence of other products, such as complementary, substitutable and clustered ones, in the assortment range
Informatyka Ekonomiczna = Business Informatics, 2021, Nr 1 (59), s. 34-59
Keywords: retailing; decision making; merchandising; shelf levels; Brand awareness; sprzedaż detaliczna; proces decyzyjny; miejsca na półkach; świadomość marki